2015
DOI: 10.3899/jrheum.150142
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Invasive Fungal Infections in Patients with Childhood-onset Systemic Lupus Erythematosus

Abstract: To our knowledge, this is the first study to characterize IFI in patients with cSLE. We identified that disease activity and current glucocorticoid use were the main risk factors for these life-threatening infections, mainly in the first years of disease course, with a high rate of fatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
3
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 37 publications
1
33
3
10
Order By: Relevance
“…We observed lower rates of serious fungal infections in our population compared with a prior report of invasive fungal infections affecting almost 4% of childhood‐onset SLE patients followed by 10 pediatric rheumatology services in Brazil . The difference may be due, in part, to the fact that our study excluded systemic candidiasis from the fungal infection outcome definition, whereas candidiasis accounted for 61% of the invasive fungal infection cases observed in the Brazilian study .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We observed lower rates of serious fungal infections in our population compared with a prior report of invasive fungal infections affecting almost 4% of childhood‐onset SLE patients followed by 10 pediatric rheumatology services in Brazil . The difference may be due, in part, to the fact that our study excluded systemic candidiasis from the fungal infection outcome definition, whereas candidiasis accounted for 61% of the invasive fungal infection cases observed in the Brazilian study .…”
Section: Discussioncontrasting
confidence: 73%
“…In studies of patients followed at tertiary care centers, it was observed that 37–57% of SLE patients had at least 1 serious infection requiring prolonged parenteral, antimicrobial therapy and/or hospitalization over an average observation period of 5 to 7 years , with an estimated annual incidence of 17 infections per 100 person‐years . We observed lower rates of serious fungal infections in our population compared with a prior report of invasive fungal infections affecting almost 4% of childhood‐onset SLE patients followed by 10 pediatric rheumatology services in Brazil . The difference may be due, in part, to the fact that our study excluded systemic candidiasis from the fungal infection outcome definition, whereas candidiasis accounted for 61% of the invasive fungal infection cases observed in the Brazilian study .…”
Section: Discussioncontrasting
confidence: 61%
“…Twenty-two cases were proven IFI, and six of them were Aspergillosis involving the lungs, CNS, and myocardium. e most important types of IFI leading to death in these series were eight cases of aspergillosis and six cases of candidiasis [5]. Some researchers focused specifically on evaluating invasive aspergillosis (IA) in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among all immunosuppressants, our study found that only steroid use—including intravenous administration and a daily oral dose of over 7.5 mg—represented an independent risk factor for severe HSV infection. Several studies have referred to systemic glucocorticoid as a risk factor for SLE infection through many pathogens, including bacteria, fungi and viruses 20–22. Among viruses, systemic steroid use has been associated with HZV,23 human papillomavirus21 and human cytomegalovirus,24 whereas little attention has been given to HSV.…”
Section: Discussionmentioning
confidence: 99%